One-pot hydrothermal synthesis of octahedral CoFe/CoFe2O4 submicron composite as heterogeneous catalysts with enhanced peroxymonosulfate activity. Issue 24 (1st June 2016) - Sun, Haiming; Yang, Xijia; Zhao, Lijun; Xu, Tianhao; Lian, Jianshe
Abstract : The unique octahedral CoFe/CoFe2 O4 submicron magnetic composite, used as a Fenton-like catalyst, exhibits superior perxoymonosulfat (PMS) activity for the degradation of organic pollutants at nearly neutral pH and room temperature. Abstract : Here we report a flexible one-pot hydrothermal synthesis of an octahedral CoFe/CoFe2 O4 submicron composite used as a superior Fenton-like catalyst for the decomposition of organic pollutants in water. As a peroxymonosulfate (PMS) catalyst, the non-toxic CoFe/CoFe2 O4 submicron composite can highly efficiently decompose Orange II (30 mg L −1, 1.5 min and 60 mg L −1, 3 min). Especially, the CoFe/CoFe2 O4 submicron composite exhibits better generalization for the degradation of different organic pollutants and excellent reusability due to its large size and structural stability. Furthermore, its high saturation magnetization (123.7 emu g −1 ) makes it convenient to magnetically separate from aqueous phase after catalysing the reaction, and its relatively large size is conducive to solving or minimizing secondary pollution. Meanwhile, the probable mechanism of PMS activation with CoFe/CoFe2 O4 catalyst is proposed.